Exposure of Fishery Resources to Environmental and Socioeconomic Threats within the Pantanal Wetland of South America - Cleber JR Alho; Roberto E Reis (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
The huge Pantanal wetland, located in the central region of South America, mainly in Brazil, formed by the Upper Paraguay River Basin, comprising 150,355 km² (approximately 140,000 km² in Brazil), is facing environmental and socioeconomic threats that are affecting fish populations and fishery resources. The Paraguay River and its tributaries feed the Pantanal wetland, forming a complex aquatic ecosystem, harboring more than 260 fish species, some of them with great subsistence and commercial values to regional human communities. Sport fishing is also preeminent in the region. The natural ecosystems and the increasing human population that depend on them are at risk from a number of identified threats, including natural habitat disruptions and overfishing. Fishing catches have been decreasing, as has the size of captured fish. Riverine vegetation, which is periodically flooded during the high-water season, forming feeding and reproductive grounds for some fish species, has been affected by deforestation and other impacts. Conversion of natural vegetation for human use and wild fires are severe and have become part of the annual cycle of ranch owners. Flooding dynamics have been threatened by infrastructure, including small hydroelectric plants on the riverheads.